Cellular transcripts regulated during infectinos with highly pathogenic H5N1 avian influenza virus in 3 host systems. - Balasubramanian, Vinod R.M.T; Syed Hassan, Sharifah; Omar, Abdul Rahman; Mohamed, Maizan; M. Noor, Suriani; Mohamed, Ramlan; Othman, Iekhsan (BioMed Central, 2011)
BACKGROUND: Highly pathogenic Avian Influenza (HPAI) virus is able to infect many hosts and the virus replicates in high levels in the respiratory tract inducing severe lung lesions. The pathogenesis of the disease is actually the outcome of the infection as determined by complex host-virus interactions involving the functional kinetics of large numbers of participating genes. Understanding the genes and proteins involved in host cellular responses are therefore, critical for the elucidation of the mechanisms of infection.